Preparation of carboxymethylcellulose from nata de coco and its assessment as potential food additive - Manguiat, Lydia S.; Sabularce, Veronica O. (1996.)
The suitability of nata de coco as raw material preparation of food-grade carboxymethyl-nata (CMN) was investigated. Four experiments were conducted to determine the effect of various conditions in the carboxymethylation of nata cellulose. The concentration of NaOH, mercerization time, shredding time during mercerization and etherification, and the concentration of monochloracetic acid significantly affected the physico-chemical properties of CMN, namely: degree of substitution (DS), viscosity, degree of polymerizatio (DP), and solubility. The best treatment combination selected consisted of: 40% NaOH, 60 min mercerization time, 60 min shredding time during mercerization and etherification, and 1.35g/ml CICH2COOH was used to produce CMN of acceptable characteristics. The developed CMN was found comparable to a commercial carboxymethylcellulose (CMC) in terms of physico-chemical and viscosity properties, except for purity which was found lower than USFDA standard. The product in powdered form was grayish-white in color, had a DS of 0.501, DP of 538.15, viscosity of 73 cps (2%, RT), and solubility of 78%. The viscosity characteristics of CMN solution were found to be affected by concentration, temperature, pH, and other treatments such as heating and boiling. Decrease in viscosity observed during heating was found to be reversible. On the other hand, low viscosity was generally observed in CMN solutions under acidic condition. The potential of CMN as food additive was assessed in three food samples, namely, peanut butter, mayonaise, and banana catsup. CMN was observed to impart stability and thickness to peanut butter, thickness/body to mayonaisse and was able to control syneresis in banana catsup.
Thesis (MS Food Science)--University of the Philippines Diliman.
Keywords: Nata de coco